Ischnomesus harrietae sp. nov., a new benthic asellote (Crustacea: Isopoda: Ischnomesidae) from bathyal bottoms of the southern Bay of Biscay - Kavanagh, Fiona A.; Frutos, Inmaculada; Sorbe, Jean Claude (Zootaxa, 2015)
A new species of Ischnomesidae (Crustacea: Isopoda: Asellota), Ischnomesus harrietae sp. nov. is described from the southern Bay of Biscay. This new species is distinctive due to the presence of numerous pedestal setae arranged in longitudinal rows on pereonite 5. Because of this morphological peculiarity, it can be easily distinguished from the four other Ischnomesus species previously reported from bathyal/abyssal bottoms of the European continental margin. Within its known distributional area, the new species inhabits sandy and muddy bottoms between 619 and 1099 m, with a maximum abundance of 41.8 individuals per 100 m2 recorded at approximately 700 m on the Arcachon Plateau. Another new species is also reported, Ischnomesus sp.1, represented by one specimen only and briefly described. An identification key to European species of Ischnomesus is provided.